Diagnosis in the profession of pastoral caregiving : in search of a theological anthropological framework for Christian spiritual assessments in clinical practice - Hunt, Sonya Francis (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.